2016
DOI: 10.1038/eye.2016.244
|View full text |Cite
|
Sign up to set email alerts
|

Difluprednate versus prednisolone acetate for inflammation following cataract surgery in pediatric patients: a randomized safety and efficacy study

Abstract: Purpose To evaluate safety and efficacy of difluprednate 0.05% ophthalmic emulsion for treatment of postoperative inflammation after cataract surgery in pediatric patients. Methods This was a phase 3B, multicentre, randomized, double-masked, active-controlled study of patients aged 0-3 years who underwent uncomplicated cataract surgery in one eye, with/without intraocular lens implantation. Patients were randomized to receive difluprednate 0.05% four times daily or prednisolone acetate 1% for 14 days post surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…; Wilson et al. ). Inflammation induced by cataract surgery may exacerbate the rate of AMD progression (Donoso et al.…”
Section: Discussionmentioning
confidence: 98%
“…; Wilson et al. ). Inflammation induced by cataract surgery may exacerbate the rate of AMD progression (Donoso et al.…”
Section: Discussionmentioning
confidence: 98%
“…Wilson ME in his study in paediatric patients (age group 0-3year) found difluprednate to be equally safe and efficient in controlling post cataract surgery inflammation as prednisolone acetate eye drops [16].…”
Section: Iop Assessmentmentioning
confidence: 99%
“…The efficacy of DEX, IND and CIP was also evaluated determined by AC inflammation, conjunctival hyperaemia, corneal and lid oedema, ocular infection, pain, photophobia and tearing in patients after cataract surgery. Currently, comparative studies of anti-inflammatory drugs for control of post cataract surgery AC inflammation have been proposed in clinic (21)(22)(23). Previous study has evaluated the efficacy of intracameral dexamethasone predisposes to glaucoma after pediatric cataract surgery (24).…”
Section: Discussionmentioning
confidence: 99%